(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper explores the economic philosophy of Jainacharya 108 Shri Vidyasagar Ji in the context of moving towards a self-reliant India, with a particular focus on the healthcare sector. Shri Vidyasagar ji emphasized on the principles of self-reliance, social justice and holistic development. By analyzing their economic principles through the lens of health care, this paper aims to highlight the importance of indigenous medicine, sustainable health care practices and equitable access to health services in achieving the goal of a self-reliant India.